Upper Airway Stimulation Response in Older Adults with Moderate to Severe Obstructive Sleep Apnea. (October 2019) - Withrow, Kirk; Evans, Sean; Harwick, John; Kezirian, Eric; Strollo, Patrick
Objective: To evaluate the impact of age on safety, efficacy, and usage of upper airway stimulation (UAS). Study Design: Multicenter observational study. Setting: Thirteen US hospitals and 3 German hospitals. Subjects and Methods: The ADHERE registry is a multicenter database enrolling patients undergoing UAS implantation from October 2016 to April 2018. Outcome measures included the Epworth Sleepiness Scale, apnea-hypopnea index (AHI), therapy usage, and complications. Data were segmented by age (<65 vs ≥65 years). Results: Younger adults (n = 365) were a mean ± SD 52.7 ± 7.9 years old and 82% male, with a body mass index of 29.6 ± 3.8. Older adults (n = 235) were 71.1 ± 4.8 years old and 71% male, with a body mass index of 28.8 ± 3.8. Baseline AHI was similar (younger, 36.2 ± 15.9; older, 36.1 ± 14.8). Both groups had lower AHI at 12 months versus baseline ( P < .001), but the older group showed a greater reduction (7.6 ± 6.9 vs 11.9 ± 13.4, P = .01). The Epworth Sleepiness Scale score decreased from 12.3 ± 5.4 to 7.1 ± 4.8 ( P < .001) among younger adults and from 10.7 ± 5.7 to 6.3 ± 4.4 ( P < .001) among older adults. Usage was slightly higher among older adults (6.0 ± 2.0 vs 5.4 ± 2.1 hours/night, P = .02). Surgical time was similar between younger patients (2.4 ± 0.7 hours) and older patients (2.3 ± 0.7 hours, P = .40), with comparably low complications. Conclusion: AHI reduction and therapy usage were found to be somewhat higher among patients aged ≥65 years who were treated with UAS. Surgical complications were low, in contrast to traditional sleep surgery.